factorise -
![{x}^{3} - {10 x }^{2} - 53x - 42 {x}^{3} - {10 x }^{2} - 53x - 42](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D++-++%7B10+x+%7D%5E%7B2%7D++-+53x+-+42)
Answers
Answered by
1
x³ - 10x² - 53x - 42
= x³ + x² - 11x² - 11x - 42x - 42
= x²(x + 1) - 11x(x + 1) - 42(x + 1)
= (x + 1)(x² - 11x - 42)
= (x + 1)(x² - 14x +3x - 42)
= (x + 1){x(x - 14) + 3(x - 14) }
= (x + 1)(x + 3)(x - 14)
= x³ + x² - 11x² - 11x - 42x - 42
= x²(x + 1) - 11x(x + 1) - 42(x + 1)
= (x + 1)(x² - 11x - 42)
= (x + 1)(x² - 14x +3x - 42)
= (x + 1){x(x - 14) + 3(x - 14) }
= (x + 1)(x + 3)(x - 14)
Similar questions